The Role of Mechanics in the Study of Lipid Bilayers - Steigmann, David J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is the first collection of lipid-membrane research conducted by leading mechanicians and experts in continuum mechanics. It brings the overall intellectual framework afforded by modern continuum mechanics to bear on a host of challenging problems in lipid membrane physics. These include unique and authoritative treatments of differential geometry, shape elasticity, surface flow and diffusion, interleaf membrane friction, phase transitions, electroelasticity and flexoelectricity, and computational modelling. .
Mechanics and Physics of Lipid Bilayers -- The Role of Mechanics in the Study of Lipid Bilayers: Elasticity and Hereditariness -- Lipid Membranes: From Self-Assembly to Elasticity -- The Geometry of Fluid Membranes: Variational Principles, Symmetries and Conservation Laws -- On the Computational Modeling of Lipid Bilayers Using Thin-Shell Theory -- Onsager's Variational Principle in Soft Matter: Introduction and Application to the Dynamics of Adsorption of Proteins onto Fluid Membranes.
Keywords: Mechanics, Applied; Solids; Geometry, Differential; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Solid Mechanics; Differential Geometry; Engineering Thermodynamics, Heat and Mass Transfer